1997
DOI: 10.1021/jp963731n
|View full text |Cite
|
Sign up to set email alerts
|

Depletion Kinetics of Niobium Atoms in the Gas Phase

Abstract: The gas phase depletion kinetics of Nb(a6D J ,a4F J ) in the presence of O2, SO2, CO2, N2O, and NO are reported. Niobium atoms were produced by the 248 nm photodissociation of Nb(C5H5)(CO)4 and detected by laser-induced fluorescence. The ground term of Nb(4d45s a6D J ) reacts at or above the collision rate with all of the aforementioned oxidants. The first excited term, Nb(4d35s a4F J ), is not as reactive with these oxidants. Results are interpreted in terms of long-range attractions and valence interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 54 publications
0
46
1
Order By: Relevance
“…Similar unimolecular reaction theory calculations were used to estimate k 0 for the reaction of the Nb atom with N 2 . McClean et al 18 have reported k 0 ϭ(2.6Ϯ0.3) ϫ10 Ϫ32 cm 6 s Ϫ1 for this reaction in Ar buffer gas at 296 K. Using the theoretically predicted properties of NbN 2 described in Sec. III B, we calculated k 0 ϭ1.3 ϫ10 Ϫ31 cm 6 s Ϫ1 , assuming strong collisions.…”
Section: Pressure Dependence Of Rate Coefficientsmentioning
confidence: 97%
“…Similar unimolecular reaction theory calculations were used to estimate k 0 for the reaction of the Nb atom with N 2 . McClean et al 18 have reported k 0 ϭ(2.6Ϯ0.3) ϫ10 Ϫ32 cm 6 s Ϫ1 for this reaction in Ar buffer gas at 296 K. Using the theoretically predicted properties of NbN 2 described in Sec. III B, we calculated k 0 ϭ1.3 ϫ10 Ϫ31 cm 6 s Ϫ1 , assuming strong collisions.…”
Section: Pressure Dependence Of Rate Coefficientsmentioning
confidence: 97%
“…character [4]. Experiments with vanadium [6], titanium [3,7], molybdenum [2,17], and niobium [25] have been performed recently which generally support this model.…”
Section: Discussionmentioning
confidence: 79%
“…1 For this reason, a fair amount of kinetic studies have been carried out for reactions of gas-phase neutral transition metal atoms with small oxygen-containing molecules (OX). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In several studies, the reaction rate constants for some low-lying electronically excited states 21 have been determined, as well as those for the ground states. 2-7, 11, 14-16 Although the excited states usually showed larger reaction rate constants than the ground states, some studies showed higher reactivities of the ground states, and suggested that the electron configuration plays a more important role than the energy.…”
Section: Introductionmentioning
confidence: 99%
“…2-7, 11, 14-16 Although the excited states usually showed larger reaction rate constants than the ground states, some studies showed higher reactivities of the ground states, and suggested that the electron configuration plays a more important role than the energy. 15,16 To understand the oxidation reactions of the transition metal atoms, two reaction mechanisms have been proposed. One is a direct oxygen abstraction mechanism.…”
Section: Introductionmentioning
confidence: 99%